(untitled) (المجلة الدولية للبحوث العلمية, 2024)
This systematic review aimed to conclusively investigate the effect of continuous intrusive force application on human pulpal blood flow (PBF). It is a well-established fact that applying a severe orthodontic force for an extended period can cause irreversible pulpitis and necrosis in the pulp by accelerating the inflammation process. In contrast, utilizing moderate and intermittent forces allows for ample tooth movement, limits pulp damage, and facilitates pulp healing. Materials and methods: A comprehensive search of published studies was conducted in several electronic databases such as MEDLINE, PubMed, EMBASE, Scopus, Web of Science, CINAHL, and the Cochrane Database of Systematic Reviews, as well as Google Scholar. The search was conducted without limitations to find published studies. The results showed that orthodontic forces can lead to a decrease in pulpal blood flow, which causes a reduction in tooth sensitivity. This reduction is indicated by an increase in response thresholds and more negative responses to tooth sensitivity tests. Conclusion: applying a severe orthodontic force over a prolonged period of time can lead to irreversible pulpitis and necrosis in the pulp due to an increase in the inflammation process. However, using moderate and intermittent forces can facilitate sufficient tooth movement while minimizing damage to the pulp. This highlights the importance of the endodontic-orthodontic interface and the need to consider dental pulp health during orthodontic treatment to avoid dental trauma.